The Human Right to Water in Law and Implementation - Norbert Brunner (Laws, 2015)
Recent concerns about alleged insufficient water provision to the poor in Detroit, USA, has put the Human Right to Water (HRW) into the international discussion. The paper asks: “To what extent did international human rights treaties make HRW judiciable?” and “How did government policies implement it?” In a cross-country comparison of performance indicators, merely accepting HRW has not been helpful in promoting affordable access to potable water or sanitation facilities close to the home, amongst the reasons being deficiencies in water-governance. Case-law confirmed that with respect to affordable access HRW obliges governments to a “progressive realization” only, also in countries accepting HRW (India, South Africa). The paper focuses on the resulting positive state obligation to establish funding programs for better water and sanitation services and analyzes funding policies by a mathematical model of policy goals. It identifies two viable goals namely the successful support for the poor, as in developing countries, and the most economic use of public funds, as in industrialized countries. Other goals conceivable for the model have been tried in the past and failed.